Stosunki polityczne między królestwem Kastylii a emiratem Granady 1246-1275 - Malinowski, Mariusz (Acta Universitatis Lodziensis. Folia Historica, 2000)
In the second half of the thirteenth century, in the Spanish South appeared a very particular organism, Islamic and very Andalusian. The birth of the emirate of Granada in 1246 was an result of the policy of Castile in the early Middle Ages. This policy based in the territorial conquest and, at the same time, tried to gain to the kingdom some new vassals. It was the main idea of Ferdinand III, who was a wise man which tried to make the Cristian and Muslim habitants of the recently conquered Andalusie live together in peace. This idea was stopped by his death in 1252. Ferdinand’s son, Alphons X, was a man with great ambitions and aspirations. The leitmotif of his reign were intents to gain the emperor’s crown. But, at the same time, he never refused the idea of the territorial expansion of Castile. His expansionism became soon dangerous to the Spanish Muslims. First, the king started to impede the life of the mudejares from the Cristian territories. This activity provoked a reaction of the emir of Granada, Muhammad I who was afraid that the next step would lead the Castilian king towards his country. Muhammad I started in the winter of 1264 an insurecction of the Andalusian mudejares. Alphons X put down the rebellion in the first months of 1265, but the situation between his kingdom and Granada was still very difficult. Alphons X was preparing a war with Muhammad I, in order to finish the existence of the last big Muslim state in the Peninsula. Then he received a surprising offer from a very strong Granadian family, named Ashqilula, deceived by the emir’s activity during the recent insurrection. The Ashqilula family, also personal enemies of the emir, offered to the king of Castile their support in the combat with Granada. The emir, scared about this, decided to exchange the neighbour state of Murcia for the kings’ refusal for the Ashqilula’s oITer. Murcia was under Castilian protectorate since 1243, but it existed with some autonomy only thanks to Granadian support. The treaty was firmed in 1265 in Alcala de Benzaide. Then Murcia was incorporated by Castile and Muhammad I met Alphons X in January of 1266, but there he discovered that the Spanish king did not want to keep his promise confirmed in the treaty. Surprisingly, Muhammad I was visited by a big Castilian noble, representing a group of political opposition towards Alphons X, composed mainly of the family of Lara. They started to be for Muhammad I the same arm against Alphons X as the Ashqilula family used to be against himself. Alphons X used to disregard the protests of his nobles and to listen to them only when he needed them. In 1272 the families Lara, de Haro and others put a confederation and they went out to Granada, after gaining by trick some money from Alphons X, then firmed some treaty of cooperation with Muhammad I, who became their feudal senior. The Spanish nobles supported the emir in some military excursion against the Ashqilula, but soon the situation changed. In the next year Muhammad I died, and was supplied by his son, Muhammad II. At the same time, the Castilian king tried to bring the opposition back, with promises and menaces. Alphons X never wanted to leave the Ashqilula alone, in order to let the emir beat them. And he disposed of the great advantage in comparison with Muhammad II, beacause the goods of his collaborators, absents in Castile, were still inside his own country, which made the menaces very real. The time was passing and the Castilian families in Granada started to change their position. The reason they went to Granada was only to press the king in order to give them some economic privileges. In Cordoba in 1274 the nobles, now keeping their king’s side, obliged Muhammad II, by trick, to accept worse conditions of the peace, without any gratification. The emir was very deceived and his reaction for the humiliate situation was the claim for the Moroccan help. The sultan Abu Yusuf came to the Peninsula with some seventeen thousands armed men, in May of 1275. This was the finish of the first scene of the relations between Castile and Granada. The frontier was established by the Muslims which decided to attack their neighbour. It was not an act of aggression, but the opposite. Granada was obliged to defend herself against the aggressive plans of a king whose ambitions were not satisfied in other occasions, like the combat for the imperial crown or, also failed, African excursions. The circumstances did not let Alphons X realize his plan, but he always had an advantage in comparison with emirs, like in the Lara’s case. In spite of this, the emirate’s aspirations was higher than only to be a financial supporter of Castile, so in 1275, when its role was diminishing quickly, its governors exposed once again its existence as the main problem of the political medieval history of the Peninsula.